Usulan Peningkatan Kinerja Karyawan di PT. X Menggunakan Metode DILO - Nico Tanaya; Tanti Octavia (Jurnal Titra, 2017)
PT. X is a subsidiary of X-Group engaged in the manufacture of plasticbased cosmetic packaging. PT. X wants to improve performance in blow and injection molding departments. Improvement is needed to apply since the workers’ cost is high. The alternatives of solutions that can be done are the  reductions of workers number or increasing the workers performance. In this research, the DILO (Day in the life of) method is applied to determine what activities are carried out during his working hours. The result shows that there are any differences from the actual and standard condition which is given by the company. The differences range of supervisors is 0% - 31%, as foremen is 2% - 21%, MTP technicians is 2% - 38%, machine technicians is 2% - 24%, administration staff is 0% - 26%. Relayout is also done in order to increase the performance of MTP technicians. Giving checklog and CCTV to related departments are also proposed to suppress workers’ lateness.